(untitled) (Global Journal of Medical Research, 2016)
Prelabor rupture of the fetal membranes (PLROM) is common obstetric problem and one of the most common clinical event where a pregnancy can turn into a high risk situation for mother as well as fetus. Present study was undertaken in a rural tertiary care institute located in central India with the aim to study the distribution and correlation of socio-demographic factors in PLROM. The overall incidence of PLROM is 6.02% of all deliveries during the study period. Majority belonged to age group of 21-25 years (57.62%). Occurrences of PROM was more among booked cases (61.90%). The incidence of PLROM was more in primigravida.